The Relationship Between Interpersonal Communication Skills and Student Problem-Solving Ability in Chemistry Learning - Fadilah, Astri; Ridwan, Achmad; Rahmawati, Yuli (Universitas Negeri Medan, 2025)
Problem-solving in chemistry is a multifaceted process influenced by both cognitive and social factors, including students’ interpersonal communication skills. This study aimed to examine the relationship between students’ interpersonal communication skills and their problem-solving ability in chemistry learning. A quantitative correlational design was employed, involving 157 eleventh-grade students from SMA Labschool Jakarta, Cibubur, and Cirendeu. Students’ problem-solving ability was measured using a multiple-choice multiple-answer (MCMA) test, while their interpersonal communication skills were assessed using the Interpersonal Communication Competence Scale (ICCS). The results showed a significant but weak positive correlation (r = 0.294) between the two variables, indicating that students with stronger interpersonal communication skills tend to perform better in solving chemistry problems. Although the contribution of interpersonal communication was relatively small, it suggests that social interaction and communicative engagement play a meaningful role in supporting cognitive performance. These findings underscore the importance of fostering interpersonal communication within chemistry education to enhance students’ problem-solving outcomes.